2000
DOI: 10.1046/j.1365-2818.2000.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

An efficient algorithm for measurement and correction of chromatic aberrations in fluorescence microscopy

Abstract: Even the best optical microscopes available on the market exhibit chromatic aberrations to some extent. In some types of study, chromatic aberrations of current optics cannot be neglected and a software correction is highly desirable. This paper describes a novel method of chromatic aberration measurement and software correction using sub‐resolution bead imaging and computer image analysis. The method is quick, precise and enables the determination of both longitudinal and lateral chromatic aberrations. Correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 14 publications
(24 reference statements)
2
53
0
Order By: Relevance
“…Chromatic aberration has previously been measured by Kuzubek and Matula (2000) using florescent dyed beads. These are then imaged in 3D, when their centroids are estimated.…”
Section: Measuring Lateral Chromatic Aberrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatic aberration has previously been measured by Kuzubek and Matula (2000) using florescent dyed beads. These are then imaged in 3D, when their centroids are estimated.…”
Section: Measuring Lateral Chromatic Aberrationsmentioning
confidence: 99%
“…The models used are again surface approximations, which are far from optimal solutions, especially since only a limited number of control points are available to estimate the surface parameters. An algorithm for the measurement and compensation of both LCA and ACA has been proposed for fluorescence microscopy by Kuzubek and Matula (2000), and for electron microscopes by Freitag et al (2005). These techniques are not transferrable to images acquired with regular imaging systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such approach may not be practical since it requires taking three pictures for each channel under different camera settings. Kozubek and Matula [4] show how to correct for both types of aberrations in the environment of fluorescent microscopy; however, this method cannot be applied for camera imaging systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a more general assumption on the nonrigid transformations between multiple channels could lead to further improvement. This may involve the use of fluorescent beads (18) and design of different computational methods. Registering the other color images to the DAPI image may be least optimal because the optical performance of the microscope system is most different in the ultraviolet/blue region where DAPI excites and emits.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, each object in the specimen also changes its off-axis position when imaged with different wavelengths, resulting in lateral chromatic aberration. Many studies conducted on this kind of error have demonstrated that even the best available objectives with high numerical aperture produce axial and lateral chromatic aberration (18). For M-FISH imaging instruments, the effect of chromatic aberration becomes even more severe.…”
Section: Sources Of Misalignmentmentioning
confidence: 99%